2010
DOI: 10.1111/j.1365-2966.2009.16210.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectral variability in the ultraluminous X-ray source Holmberg IX X−1

Abstract: We use XMM–Newton and Swift data to study a spectral variability in the ultraluminous X‐ray source (ULX), Holmberg IX X−1. The source luminosity varies by a factor of 3–4, giving rise to corresponding spectral changes which are significant, but subtle, and not well tracked by a simple hardness ratio. Instead, we co‐add the Swift data in intensity bins and do full spectral fitting with disc plus thermal Comptonization models. All the data are well fitted by a low temperature, optically thick Comptonizing corona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 48 publications
15
56
0
Order By: Relevance
“…This would mean that the ULX is less extreme in luminosity than previously reported and possibly more similar to the bulk population of typical ULXs in the nearby Universe (e.g. Gladstone et al 2009;Vierdayanti et al 2010;Middleton et al 2011;Pintore & Zampieri 2012;Bachetti et al 2013;Sutton et al 2013b;Walton et al 2013a;Pintore et al 2014;Middleton et al 2015). This would imply that our previous highly tentative mass estimate for the BH relative to NGC 1313 X-2 should be lowered to a factor of ∼2-3.…”
Section: Discussionmentioning
confidence: 81%
“…This would mean that the ULX is less extreme in luminosity than previously reported and possibly more similar to the bulk population of typical ULXs in the nearby Universe (e.g. Gladstone et al 2009;Vierdayanti et al 2010;Middleton et al 2011;Pintore & Zampieri 2012;Bachetti et al 2013;Sutton et al 2013b;Walton et al 2013a;Pintore et al 2014;Middleton et al 2015). This would imply that our previous highly tentative mass estimate for the BH relative to NGC 1313 X-2 should be lowered to a factor of ∼2-3.…”
Section: Discussionmentioning
confidence: 81%
“…Luminosity is often used as a predictor of accretion rate, and in BHBs it is well established that the spectral state is not set by the luminosity alone (for a review, see Remillard & McClintock 2006). Grisé et al (2010) and Vierdayanti et al (2010) have shown that the spectral state varies at a single luminosity for the ULXs Holmberg II X-1 and Holmberg IX X-1, respectively, suggesting that an additional parameter beyond accretion rate can vary for individual sources. It would be interesting to discover whether this trait is common to other ULXs and, thus, an additional parameter is needed to set the accretion state of a given source.…”
Section: Introductionmentioning
confidence: 99%
“…This multiwavelength data sample spans 5 yr. We note that HoIX X-1 is known to show X-ray variations of factors of 4-5 over days to years (Vierdayanti et al 2010;Luangtip et al 2016). Unfortunately, the only available multiwavelength data set that was taken of this object includes X-ray data from Chandra that suffer from severe pileup and are therefore unusable for the X-ray-fitting portion of this analysis (Grisé et al 2011).…”
Section: Spectral Energy Distributionmentioning
confidence: 99%